1997
DOI: 10.1007/bf01007831
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus and branch retinal vein occlusion

Abstract: Branch retinal vein occlusion (BRVO) is often associated with arteriosclerosis. Typically the occlusion occurs at an arteriovenous crossing. We report a case of a previously healthy patient who developed a BRVO. Funduscopy and fluorescein angiography suggested an intravascular thrombus as the cause of the occlusion. The investigations performed were positive for systemic hypertension and hyperlipidaemia. After 2 months, fundus examination revealed disappearance of the intravascular thrombus, resolution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The pathomechanisms described above raise some questions that are listed below: If we assume the mechanical compression of the vein being important: Why is a BRVO sometimes reversible [19]?Why do BRVOs not always occur at A/V crossings [19]?Why is a distinct vein compression histologically not always visible [20]?Why do we only extremely rarely find a thrombus [4, 21, 22]? And if a thrombus is present why do we find it rather downstream of A/V crossings [23]?…”
Section: Open Questions Challenging the Present Conceptsmentioning
confidence: 99%
“…The pathomechanisms described above raise some questions that are listed below: If we assume the mechanical compression of the vein being important: Why is a BRVO sometimes reversible [19]?Why do BRVOs not always occur at A/V crossings [19]?Why is a distinct vein compression histologically not always visible [20]?Why do we only extremely rarely find a thrombus [4, 21, 22]? And if a thrombus is present why do we find it rather downstream of A/V crossings [23]?…”
Section: Open Questions Challenging the Present Conceptsmentioning
confidence: 99%
“…Retinal vascular occlusions may be due to a combination of various mechanisms such as degenerative changes of the vessel wall, abnormal hematological factors or an abnormal perivascular status. It is most likely that the majority of retinal vascular occlusions, particularly in elderly patients, are primarily secondary to underlying cardiovascular diseases [1,2,26,29,30]. Hence, it seems plausible that screening for thrombophilic disorders in patients with retinal vein or artery occlusion should be selective.…”
Section: Introductionmentioning
confidence: 98%
“…BRVOs occur at an arteriovenous crossing, with strong evidence that an intravenous thrombus is the penultimate cause of the occlusion to venous outflow and that there is further active propagation of the thrombus downstream. [8][9][10] It is this occlusion that is responsible for the delay in retinal blood flow through the occluded segment and the subsequent VEGF upregulation and elevation in hydrostatic pressure that produce the retinal changes seen clinically. 32 Results from the BRAVO and subsequent extension studies have shown that the VEGF upregulation can be controlled with intraocular injections of ranibizumab with good initial effects on visual acuity; however, injections in many patients need to be continued for years.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the thickened and rigid arteriosclerotic arterial wall compresses the vein, resulting in turbulence in blood flow and endothelial damage leading to the formation of a local thrombus. [8][9][10] The evidence that a thrombus is the cause of the obstruction to the venous outflow in BRVO is much stronger than in central retinal vein occlusion (CRVO), where both the cause and site of the venous obstruction still remain controversial. [11][12][13] The largest histopathological study of BRVOs showed evidence of a fresh or recanalized thrombus within the retinal vein at the site of the obstruction in all nine cases examined.…”
mentioning
confidence: 99%